2013
DOI: 10.5336/medsci.2012-30150
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of the External Human Ear: A Geometric Morphometric Study

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The aim of this study was to identify the shape variability of the external ear. Variability in the shape of the ear was investigated based on the type of ear, gender and facial side in terms of the shape of the helix and antihelix and the concha. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : A landmark-based geometric morphometric technique was used to analyze the external shape of the ear. The study included 330 (177 females and 153 males)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Similarly, quantification of measurement error in longitudinal studies are necessary in that developmental changes may be masked by measurement error. Measurement error in the present study is not of serious concern due to the low percent measurement error, which is comparable with landmark reliability of a geometric morphometric study on human external ear [34]. In addition, the large sample size and longitudinal nature of this study allowed for high power to detect developmental changes in the presence of measurement error.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, quantification of measurement error in longitudinal studies are necessary in that developmental changes may be masked by measurement error. Measurement error in the present study is not of serious concern due to the low percent measurement error, which is comparable with landmark reliability of a geometric morphometric study on human external ear [34]. In addition, the large sample size and longitudinal nature of this study allowed for high power to detect developmental changes in the presence of measurement error.…”
Section: Discussionsupporting
confidence: 56%
“…Most of the medical studies are related to the examination of the geometrical properties of an organ or organism [1,8,15]. Commonly, quantitative or qualitative data sets in the statistical analysis have consisted of measuring values, today's the appearance or shape of an organ or organism has been used as input data by the development of imaging techniques [7].…”
Section: Introductionmentioning
confidence: 99%
“…The surface of this structure is characterized by protrusions and depressions [47]. Auricula is composed of three main components: helix-antihelix, cavum concha and lobulus auriculae [31].…”
Section: Introductionmentioning
confidence: 99%
“…There are a limited number of studies in the literature for auricula by using geometric morphometric methods in adult human beings [31,33]. However, no study has been found in which auricula is analysed with geometric morphometric methods based on the foetal period.…”
Section: Introductionmentioning
confidence: 99%